2007
DOI: 10.1001/archopht.125.3.354
|View full text |Cite
|
Sign up to set email alerts
|

Primary Intraocular Lens Implantation in Pediatric Uveitis

Abstract: To evaluate the visual outcome and postoperative complications of cataract surgery with posterior chamber intraocular lens implantation in children with uveitis. Design: A multicenter, retrospective, interventional case series. The setting included 3 medical centers in Israel. The interventions were cataract surgery and intraocular lens implantation. Aggressive preoperative and postoperative systemic and topical anti-inflammatory treatment was instituted. The main outcome measures included postoperative inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 33 publications
1
25
1
2
Order By: Relevance
“…1 It occurs in 52% of children with uveitis 2 and is the most frequent cause of vision loss. 2 Furthermore, this reduction of visual acuity in children can have a major impact on behavioral development.…”
Section: Introductionmentioning
confidence: 99%
“…1 It occurs in 52% of children with uveitis 2 and is the most frequent cause of vision loss. 2 Furthermore, this reduction of visual acuity in children can have a major impact on behavioral development.…”
Section: Introductionmentioning
confidence: 99%
“…An example of such a measure is an anterior vitrectomy at the time of cataract surgery. Postoperative complications which have been observed in uveitis, sometimes after several months or years of quiescence, include the development of thick secondary retrolental membranes, hypotony, ERM and macular edema [12,13,14,15,16]. …”
Section: Discussionmentioning
confidence: 99%
“…In a time domain OCT study of children with JIA, 84% were found to have signs of maculopathy [7]. Following cataract surgery, in the absence of a vitrectomy, overt cystoid macular edema is observed in 10-40% of children [12,13,14]. Following a pars plana vitrectomy, there is resolution of preoperative macular edema in more than 50% of children indicating the value of this additional step [20,24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperativ neigen diese Augen, auch ohne IOL, zu zahlreichen Komplikationen mit foudroyanter Fibrinreaktion, posterioren Synechien, retrolentalen Membranen, zystoidem Makulaçdem, Hypotonie und Phthisis bulbi [6,23]. Mit dem konsequenten Einsatz moderner immunsuppressiver Strategien werden aber erstmals auch günstige Ergebnisse nach IOL-Implantation bei Kindern mit JIA-assoziierter Uveitis berichtet [15,21]. In einer großen retrospektiven Studie konnte gezeigt werden, dass unter strikter Kontrolle der Entzündungsaktivität mit Intraokularlinsen in vielen Fällen sehr gute Visusergebnisse erzielt werden, obwohl Komplikationen nicht vollständig vermieden werden [14].…”
Section: Kunstlinsen-implantationunclassified